Uterine cervical neoplasms mass screening at the University Hospital Centre of Libreville, Gabon: Associated factors with precancerous and cancerous lesions. - Sylvain Honore Woromogo; Nathalie Ambounda Ledaga; Felicite Emma Yagata-Moussa; Astride Smeige Mihindou (PLoS ONE, 2021)
The objectives of this study were to identify the associated factors with cancerous and precancerous lesions of cervix. In Africa, the incidence of uterine cervical neoplasms varies from one region to another, where most women with uterine cervical neoplasms are seen at an advanced stage. For this reason, uterine cervical neoplasms mass screening reduces the incidence and mortality due to this disease, similar to what is being done in Europe. A cross-sectional analytical study was conducted. Socio-demographic characteristics, gynaecological-obstetrical history, risk factors, data from visual inspection with acetic acid and visual inspection with Lugol, colposcopy impressions and results of cytological analysis were performed. A simple and multiple regression were performed to establish a statistically significant difference between certain factors and the presence of precancerous or cancerous lesions of uterine cervical. In this study, of 63 women diagnosed histologically, 43 had precancerous lesions and 20 had cancerous lesions. we found that being older than 35, having the first intercourse before 18, having an antecedent of STI, being a widow and using of tobacco were risk factors associated with precancerous lesions (p = 0.013 with OR = 3.44 (1.22-9.73), p = 0.009 with OR = 4.07 (1.69-13.08), p < 0.001 with OR = 3.80 (1.94-7.47), p < 0.001 with OR = 9.77 (3.87-24.70) and p < 0.001 with OR = 5.47 (2.60-11.52)) respectively. Only being older than 45, being a widow and using tobacco were risk factors associated with cancerous lesions (p = 0.021 with OR = 2.01 (1.58-3.56), p = 0.02 with OR = 2.96 (2.10-3.87), p = 0.041 with OR = 1.98 (1.46-2.44)) respectively. Among participants diagnosed with uterine cervical neoplasms, there was a significant association with the STI, marital status and smoking. Despite the integration of the detection of precancerous uterine cervical neoplasms lesions into health facilities in Gabon, uterine cervical neoplasms ranks second among women's cancers in terms of incidence and first in terms of mortality.